Political review of the failure of the revision of Undang-Undang Nomor 20 Tahun 2003 Tentang Sistem Pendidikan Nasional in 2023 and its impact on education in Indonesia - Boyke Azwar; Muhammad Sirozi; Sholihah Titin Sumanti (Inovasi Kurikulum, 2024)
The national education system, according to Undang-Undang Nomor 20 Tahun 2003 Tentang Sistem Pendidikan Nasional, is considered not to have undergone in-depth study and ignores various important considerations, resulting in discrimination that is contrary to the principle of justice that the government should uphold. Therefore, the government has attempted to revise the law and improve the legal framework for education in Indonesia to align with society's times and needs. However, the revision failed to enter the Priority Prolegnas in 2023. This study aims to examine the political factors that caused the failure of the revision of Law Number 20 of 2003 concerning the National Education System (SISDIKNAS) in 2023. This study uses a qualitative case study approach by analyzing various political dynamics during the revision process. The study results indicate that a combination of internal factors, such as differences of opinion between political parties and factions in the DPR, and external factors, such as pressure from interest groups and community organizations, caused the failure of the revision. This study provides an in-depth understanding of the complexity of the legislative process in Indonesia, as well as its implications for future education reform efforts. AbstrakSistem pendidikan nasional menurut Undang-Undang Nomor 20 Tahun 2003 tentang Sistem Pendidikan Nasional dianggap tidak melalui kajian mendalam dan mengabaikan berbagai pertimbangan penting, sehingga mengakibatkan diskriminasi yang bertentangan dengan prinsip keadilan yang seharusnya dijunjung tinggi oleh pemerintah. Oleh kerena itu pemerintah telah mengupayakan revisi terhadap undang-undang dan menyempurnakan kerangka hukum pendidikan di Indonesia agar lebih sesuai dengan perkembangan zaman dan kebutuhan masyarakat, namun revisi tersebut gagal masuk Prolegnas Prioritas tahun 2023. Penelitian ini bertujuan untuk mengkaji faktor-faktor politik yang menyebabkan kegagalan revisi Undang-Undang Nomor 20 Tahun 2003 tentang Sistem Pendidikan Nasional (SISDIKNAS) pada tahun 2023. Penelitian ini menggunakan pendekatan kualitatif studi kasus dengan menganalisis berbagai dinamika politik yang terjadi selama proses revisi. Hasil penelitian menunjukkan bahwa kegagalan revisi disebabkan oleh kombinasi faktor internal, seperti perbedaan pandangan antara partai politik dan fraksi di DPR, serta faktor eksternal seperti tekanan dari kelompok kepentingan dan organisasi masyarakat. Penelitian ini memberikan pemahaman mendalam mengenai kompleksitas proses legislasi di Indonesia, serta implikasinya bagi upaya reformasi pendidikan di masa depan.Kata Kunci: pendidikan; proses legislative; review politik